Policy Debate | The UN Guidelines on Forced Evictions : A Useful Soft-Law Instrument? - Miloon Kothari; Patricia I. Vasquez (Revue Internationale de Politique de Développement)
Editor’s note: These papers are a contribution to the ‘Policy Debate’ section of International Development Policy. In this section, academics, policy-makers and practioners engage in a dialogue on global development challenges. Papers are copy-edited but not peer-reviewed. Instead, the initial thematic contribution is followed by critical comments and reactions from scholars and/or policy-makers. This debate can be pursued on the Journal’s blog (http://devpol.hypotheses.org/965) where you are invited to share your reflections under your name.In the initial paper ‘Land Grabbing and the UN Guidelines on Evictions: A Promising Soft-Law Approach’, the author puts the establishment of the United Nations Guidelines on evictions in the context of growing international concerns with the negative impact of land grabbing on local populations; describes their main features; and highlights their uses in different spheres (academia, jurisprudence, development practice and human rights advocacy). He then concludes with a positive assessment of this soft-law instrument, but he also stresses that much more remains to be done to ensure the protection of international human rights standards. In her comments, Patricia Vasquez, from the Graduate Institute’s Centre on Conflict, Development and Peacebuilding, suggests that Kothari’s comprehensive evaluation of the Guidelines could benefit from a more in-depth analysis of the lessons learned in the implementation of other soft-law instruments developed in recent years to counter evictions related to land grabbing.